Theoretical investigation on an oscillating buoy WEC‐floating breakwater integrated system - Dezhi Ning; Baoming Guo; Rongquan Wang; Lin Lin (IET Renewable Power Generation, 2021)
Abstract Based on the concept of cost sharing, an oscillating buoy wave energy converter‐ floating breakwater integrated system is proposed, in which the surge or pitch motion of the front‐pontoon equipped with Power Take‐off (PTO) system is allowed. In this study, the methods of eigenfunction matching and variables separation are applied to establish a theoretical model on hydrodynamic performance of the proposed integrated system. Under the condition of optimal PTO damping, the effects of the front‐pontoon width, draft and pontoon spacing on the capture width ratio, reflection coefficient and transmission coefficient are investigated, respectively. It is found that the integrated system with surging front‐pontoon performs better on the wave energy conversion than that with pitching one, especially in the high frequency region. The peaks of capture width ratio Cw are associated with the gap resonance and the increase of front‐pontoon motion induced by the ‘hydrodynamic constructive effect’.